2016
DOI: 10.1016/j.jad.2015.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Altered resting-state functional connectivity in late-life depression: A cross-sectional study

Abstract: Background Disrupted brain connectivity is implicated in the pathophysiology of late-life depression (LLD). There are few studies in this area using resting-state functional magnetic resonance imaging (rs-fMRI). In this pilot case-control study, we compare rs-fMRI data between age-matched depressed and non-depressed older adults. Methods Older participants (≥ 55 years) with current major depressive disorder (MDD) were recruited to participate in an ongoing study of LLD, and were compared to the age-matched, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 50 publications
2
31
0
Order By: Relevance
“…The results from the real data analysis suggest that the DDT appropriately identifies problematic brain regions in major depressive disorder. The existence of differential connectivity between nodes in the AUD and VIS networks (Figure ) has previously been observed (Eyre et al, ). Further, multivariate pattern analyses have suggested that the most discriminative FC patterns lie within and across the VIS network, DMN, and affective network (Zeng et al, ).…”
Section: Resultssupporting
confidence: 70%
“…The results from the real data analysis suggest that the DDT appropriately identifies problematic brain regions in major depressive disorder. The existence of differential connectivity between nodes in the AUD and VIS networks (Figure ) has previously been observed (Eyre et al, ). Further, multivariate pattern analyses have suggested that the most discriminative FC patterns lie within and across the VIS network, DMN, and affective network (Zeng et al, ).…”
Section: Resultssupporting
confidence: 70%
“…Future work will involve investigation of the relationships among depressive symptoms, AD proteinopathies, and medical and cerebrovascular illness burden, as well as those between depression and cognitive function. Furthermore, given the role of disruption of network structure and function in depressive illness and AD [5155], future work investigating tau and amyloid accumulation in the context of both neuronal network structure and functional connectivity may provide a more thorough understanding of the pathophysiology of these symptoms in the context of other age-related brain changes.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced DMN Fc is demonstrated in LLD (Alexopoulos et al, 2012; Eyre et al, 2016; Wu et al, 2011), which may be due to aging-related brain changes (Smith, G.S. et al, 2009; Wu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Using seed-based resting-state functional connectivity magnetic resonance imaging (R-fcMRI) technique, diminished functional connectivity (Fc) within the ECN is observed in LLD and is predictive of poor treatment response, persistent depressive symptoms and executive dysfunction (Alexopoulos et al, 2012). LLD is also associated with enhanced DMN Fc in symptomatic (Alexopoulos et al, 2012; Eyre et al, 2016) but not remitted (Sexton et al, 2012) patients. Intrinsic ECN and DMN Fc changes differ based on antidepressant response, and could serve as early markers of treatment response variability in LLD (Karim et al, 2016).…”
Section: Introductionmentioning
confidence: 99%